The Fortifications at Tel Burna: Date, Function and Meaning - Shai, Yitsḥaḳ; Cassuto, Deborah; Dagan, Amit; Uziel, Joe (2012)
The first two seasons of work at Tel Burna have focused on revealing a segment of the fortification walls partially exposed along the perimeter of the upper tel. The discovery of a seventh-century silo cutting the inner wall of the fortifications provides a terminus ante quem for the wall. This discovery, in conjunction with other finds from the excavations, presents us with a unique opportunity to explore the significance and meaning of fortifications and the fortified towns along the western border of ancient Judah.